Jawabanmu

Jawaban paling cerdas!
2014-04-30T07:30:13+07:00
f(x)=px + q.
f(-2) = -2p + q = -13 dan
f(3)  =  3p + q  =  12 -
           -5p       = -25
               p = -25/-5 = 5
-2p + q = -13
⇔ -10 + q = -13
⇔ q = -13 + 10 = -3
Jadi
f(x)=px + q ⇔ f(x)=px + q menjadi f(x) = 5x - 3
                                           maka nilai f(5) = 5(5) - 3 = 25-3 = 22





1 5 1
2014-04-30T07:41:06+07:00
-2p + q = -13
 3p + q = 12      -
-5p     = -25

 P = 5 , q = -3
jadi  f(5) = p(x) + q = 5(5) + -3 = 22